Silicone oil versus gas tamponade for giant retinal tear-associated fovea-sparing retinal detachment: a comparison of outcome - Banerjee, P J (Eye (Lond), 2017)
PURPOSE: Silicone oil is the most common choice of tamponade agent used when managing a giant retinal tear (GRT). Concern exists regarding its potential detrimental effect on vision. We herein report on visual and surgical outcomes of all patients treated at Moorfields Eye Hospital for a GRT over a five year period. We further analysed a subgroup of fovea-sparing retinal detachments (RD) treated by pars plana vitrectomy (PPV) with either silicone oil or gas tamponade. METHODS: Retrospective comparative, non-randomised, cross-sectional review of patients with a new diagnosis of GRT from 1 September 2005 to 31 August 2010 RESULTS: One hundred twenty four eyes of 118 patients were identified with mean age of 45.5 years and median follow-up of 24 months. Subgroup analysis of fovea-sparing RDs (Silicone Oil n=49, Gas n=15) revealed visual loss (≥2 Snellen Lines of vision) in 49.0% (n=24) of patients managed with oil compared to 13.3% (n=2) of gas patients (P=0.019). In all, 73.3% (n=11) in the gas group achieved a final vision of 6/12 or better, compared to 36.7% (n=18) in the oil group (P=0.031). No difference was observed in eventual or primary anatomical success rate (100 vs 93.9%, and 66.7 vs 79.6%, gas vs oil, respectively, (P>0.1)). Postoperative complications were absent in 66.7% (n=10) of gas patients compared with 14.3% (n=7) of oil patients (P=0.002). Multiple variable linear regression determined tamponade choice as the only variable predictive of final visual acuity (P=0.046). CONCLUSION: Eyes with fovea-sparing GRT-related RDs managed with gas achieved a better visual outcome with fewer postoperative complications and no significant difference in anatomical success. A multicentre approach to investigate this further is advised.